ANALISIS ANALISIS MARKETING STRATEGY SAYUR ONLINE DI MASA NEW NORMAL COVID-19 - Muhammad Deni; Indah Mawarni (Jurnal Ekonomi dan Bisnis (EK dan BI), 2022)
This study aims to find out: how to apply online vegetable marketing strategy at Warung Ibu Yuli in the new normal of Covid-19. The method used in sampling is to use purposive sampling method, the analysis method used is qualitative descriptive analysis method using SWOT and QSPM matrix method. The results of this study showed that the final score after weighting in internal and external analysis there are 7 alternative strategies that have been obtained from the results of the SWOT matrix, namely (1)reminding the public periodically about the quality and price of Warung Sayur Ibu Yuli products, (2)expanding and adding information about the location and phone number or Whatsapp, (3)opening direct orders between and expanding supplier networks , (4) make and add innovations to the marketing done and packaging conducted, (5) the application of discount promos adjusted to the difference in the latest price increase of products, (6)continue to innovate on the service and supervise players in the same market periodically, (7)increase the number of orders from the number of requests. Each altenative is then analyzed using the QSPM matrix.